Option valuation - Turnbull, Stuart M. (Canada : Holt, Rinehart, and Winston of Canada, 1987)
Shows users how to do option valuation.
System requirements: IBM PC, XT, or AT; 128K; PC-DOS; 1-2 disk drives or hard disk; printer recommended.
3 copies.
Keywords: Stock options -- Software